2010
DOI: 10.1007/s10533-010-9436-3
|View full text |Cite
|
Sign up to set email alerts
|

Snow depth, soil freezing and nitrogen cycling in a northern hardwood forest landscape

Abstract: Increases in soil freezing associated with decreases in snow cover have been identified as a significant disturbance to nitrogen (N) cycling in northern hardwood forests. We created a range of soil freezing intensity through snow manipulation experiments along an elevation gradient at the Hubbard Brook Experimental Forest (HBEF) in the White Mountains, NH USA in order to improve understanding of the factors regulating freeze effects on nitrate (NO 3 -) leaching, nitrous oxide (N 2 O) flux, potential and in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(95 citation statements)
references
References 59 publications
5
89
1
Order By: Relevance
“…For example, most laboratory studies under controlled conditions did not include snow cover in their experimental designs, and soil moisture levels were usually adjusted before soil freezing (Priemé and Christensen 2001;Teepe et al 2004;Wu et al 2010a). However, snow cover has been reported to be particularly important for C and N trace gas fluxes during soil freezing and thawing (Groffman et al 2006(Groffman et al , 2011, since it can not only exert strong control on the dynamics of soil temperature and moisture (Buckeridge and Grogan 2010) but also significantly affect soil C and N turnover and soil microbial community structure and function (Feng et al 2007;Groffman et al 2011). Thus, the effects of snow cover and water from melting snow should be implemented in FTC studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, most laboratory studies under controlled conditions did not include snow cover in their experimental designs, and soil moisture levels were usually adjusted before soil freezing (Priemé and Christensen 2001;Teepe et al 2004;Wu et al 2010a). However, snow cover has been reported to be particularly important for C and N trace gas fluxes during soil freezing and thawing (Groffman et al 2006(Groffman et al , 2011, since it can not only exert strong control on the dynamics of soil temperature and moisture (Buckeridge and Grogan 2010) but also significantly affect soil C and N turnover and soil microbial community structure and function (Feng et al 2007;Groffman et al 2011). Thus, the effects of snow cover and water from melting snow should be implemented in FTC studies.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality of fine roots or lysis of freeze-damaged soil organisms (Soulides and Allison 1961), as well as an increased number of FTCs (Henry 2007) may also affect the soil DOC pool. To date, only a few field-scale studies have examined the effect of soil frost on DOC Fitzhugh et al 2001;Groffman et al 2001Groffman et al , 2010, and these have focused mainly on the release of DOC rather than its composition.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research of this nature is of great relevance to the future of American beech stands. For instance, some experimental studies have suggested that decreased snow cover in the winter (a result of increased winter temperatures) that leads to soil freezing may significantly alter the leaching of inorganic nitrogen and phosphorus in northern hardwood forests [53][54][55][56], in which American beech is frequently a component. However, there exists no clear, specific consensus in the scientific literature as to how soil ecosystems will respond to global climate change or how those changes will translate into specific changes in forest communities, insofar as we are aware.…”
Section: The Impacts Of Climate Change On American Beechmentioning
confidence: 99%